Rethinking Dąbrowski's Theory II: It's Not All Flat Here. Issue 2 (3rd April 2017) - Piechowski, Michael M.
Abstract : Unilevel disintegration, the second level in Dąbrowski's theory, does not have a structure comparable to the higher levels. It also lacks direction. If so, one is bound to ask what is developmental about it and what, in fact, is developing in level II. Two classsic studies and one of highly gifted adults show three possible kinds of emotional development on the not-so-flat plane of level II: a personal growth from black-and-white to relativistic thinking, from no sense of self to an individual self, and fulfillment of one's talents as a productive member of society. Viewing the levels as types of development makes clear that the first two levels are not precursors to advanced development.